Systems, Tridimensionality and Deconstruction: Applying Complexity to Social Anthropological Research - Ortega Senet, María Belén (MAD, 2013)
This article aims to show the applicability of ideas based on the Paradigm of Complexity that emerged from an action-research study analysing power and agency, with a group participating to the Local Power Development Program of in El Alto, Bolivia. This applicability is specified in a proposal for a complex approach of the study object and a consequent fieldwork and data analysis methodology, integrating a transdisciplinary position, a three-dimensional research design and a conceptual framework sensitive to deconstruction.